An easy to assemble microfluidic perfusion device with a magnetic clamp - Tkachenko, Eugene (2009)
We have built and characterized a magnetic clamp for reversible sealing of PDMS microfluidic chips against cover glasses with cell cultures and a microfluidic chip for experiments on shear stress response of endothelial cells. The magnetic clamp exerts a reproducible uniform pressure on the microfluidic chip, achieving fast and reliable sealing for liquid pressures up to 40 kPa inside the chip with <10% deformations of microchannels and minimal variations of the substrate shear stress in perfusion flow. The microfluidic chip has 8 test regions with the substrate shear stress varying by a factor of 2 between each region, thus covering a 128-fold range from low venous to arterial. The perfusion is driven by differential pressure, which makes it possible to create pulsatile flows mimicking pulsing in the vasculature. The setup is tested by 15 – 40 hours perfusions over endothelial monolayers with shear stress in the range of 0.07 - 9 dyn/cm(2). Excellent cell viability at all shear stresses and alignment of cells along the flow at high shear stresses are repeatedly observed. A scratch wound healing assay under a shear flow is demonstrated and cell migration velocities are measured. Transfection of cells with a fluorescent protein is performed, and migrating fluorescent cells are imaged at a high resolution under shear flow in real time. The magnetic clamp can be closed with minimal mechanical perturbation to cells on the substrate and used with a variety of microfluidic chips for experiments with adherent and non-adherent cells.